The generalized Wielandt inequality in inner product spaces - Lin, Minghua; Sinnamon, Gord (Eurasian Mathematical Journal, 2012)
A new inequality between angles in inner product spaces is formulated and proved. It leads directly to a concise statement and proof of the generalized Wielandt inequality, including a simple description of all cases of equality. As a consequence, several recent results in matrix analysis and inner product spaces are improved.